Juvenile Hormone III but Not 20-Hydroxyecdysone Regulates the Embryonic Diapause of Aedes albopictus - Batz, Zachary A.; Brent, Colin S.; Marias, Molly R.; Sugijanto, Jennifer; Armbruster, Peter A. (Frontiers in Physiology, 2019)
Diapause is an alternative developmental trajectory allowing insects to enter dormancy and persist through predictable periods of seasonally-unfavorable conditions. This crucial ecological adaptation defines the geographic and seasonal abundance of many insect pollinators, pests, and vectors. Understanding the hormonal changes by which insects coordinate the perception of external, diapause-inducing cues with the physiological mechanisms that lead to developmental arrest is a long-standing goal in biology. The hormonal regulation of diapause tends to vary by the life stage at which development arrest occurs; for example, diapause is typically regulated by ecdysteroids in larvae and pupae, and by juvenile hormones in adults. However, little is known about the hormonal control of embryonic diapause, particularly in Diptera. To address this fundamental gap, we directly measured 20-hydroxyecdysone (via LC-MS/MS) and juvenile hormone III (via GC-MS) in diapause and non-diapause eggs of the Asian tiger mosquito, Aedes albopictus. While 20-hydroxyecdysone abundance did not differ, diapause eggs had lower juvenile hormone III abundance than non-diapause eggs. These results are corroborated by transcriptional and manipulative evidence suggesting that reduced juvenile hormone III regulates diapause in this medically-important mosquito.